Utilization of Multimedia in the Islamic Education Learning Process on Student Learning Achievement at MTS Negeri 3 Aceh Barat - Yanti, Safrida; Zubaidah (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2024)
This study aims to examine the impact of multimedia integration in improving student engagement, motivation, and academic achievement in Islamic Education learning at MTs Negeri 3 Aceh Barat. This study used a quasi-experimental design, with two groups of students: an experimental group that used multimedia in the learning process and a control group that used traditional teaching methods. This study collected data through pre- and post-assessments, classroom observations, and student motivation surveys. The results showed that the experimental group that used multimedia experienced a significant increase in understanding and application of Islamic teachings, especially in real-life situations, compared to the control group. The use of multimedia, such as educational videos, interactive presentations, and digital quizzes, made learning more dynamic and interesting, which increased student engagement in the lesson. Students who were exposed to multimedia materials reported increased motivation and greater interest in Islamic Education Learning materials. The results of classroom observations also showed that students in the experimental group were more active participants and showed higher enthusiasm in class discussions. The use of interesting multimedia tools facilitated students' active involvement in discussions and applications of Islamic principles, which resulted in a deeper understanding of the material. The motivation survey also showed an increase in student motivation in the experimental group, who felt more interested and connected to the learning materials thanks to the use of multimedia. Overall, this study concluded that the integration of multimedia in Islamic Education learning has proven effective in increasing student engagement, motivation, and academic achievement. This study recommends that MTs Negeri 3 Aceh Barat continue the use of multimedia in the Islamic Education curriculum to enhance a more interactive and engaging learning experience for students.